The Role of the Gut Microbiome and the Hepatic Axis in the Pathogenesis of Metabolic Syndrome and Therapeutics - K. P. Divya; Parneet Hari; Navjot Kanwar; Navita Aggarwal; Preeti Singh Dhoat; Lu Liu; Abhinav Kanwal; Shailendra Pratap Singh (Advanced Gut & Microbiome Research)
The increased global prevalence of viral and noninfectious liver illnesses has coincided with a surge in scientific interest in gut microbiota (GM), a multispecies community of bacteria, fungi, archaea, and protozoans. Dietary nutrients that make up the host’s microbiome are responsible for maintaining intestinal homeostasis, whereas a disconnect between gut flora and nutrition might have serious consequences for digestive health. The risk of liver dysfunction was continuously elevated by changes in the commensal bacteria of the gut microbiome, which were carried to the liver via the portal vein. Insights into the role of gut microbiota in alcoholic liver disease, nonalcoholic liver disease, primary sclerosing cholangitis, and other liver disorders, as well as their link to liver cancer, continue to emerge. Systemic host defence against infections by the gut microbiota depends on the interplay between the microbiome, liver immunology, and liver disorders. Translocation of microbiota to the liver following injury and/or inflammation may mediate dysbiosis and the formation of gut microbial metabolite. This review discusses the role of the gut microbiota in connection to dysbiosis and how this knowledge might help us better understand the pathophysiology of various liver illnesses.